Peran Self-Control dalam Memoderasi Pengaruh Social Proof dan Fear of Missing Out (FOMO) terhadap Impulsive buying Produk Skincare - Sri Indah Lestari; Muhammad Daffa Zulfikar; Rahmat Maulidan; Nova Novitasari; Helmi Murtaza (Journal of Business and Economics Research (JBE), 2026)
This study aims to analyze the influence of Social Proof and Fear of Missing Out (FOMO) on impulsive buying behavior of skincare products and test the role of Self-Control as a moderating variable. The study used a quantitative approach with a survey method of 240 social media users who have purchased skincare products. The sampling technique used purposive sampling, while data analysis was carried out using Structural Equation Modeling (SEM) based on AMOS 25. The results showed that Social Proof had a significant effect on impulsive buying (C.R. = -2.052; p = 0.04), while FOMO had no significant effect on impulsive buying (C.R. = -0.544; p = 0.586). In addition, Self-Control was shown to moderate the relationship between Social Proof and impulsive buying (C.R. = 3.962; p < 0.001) and the relationship between FOMO and impulsive buying (C.R. = 3.867; p < 0.001). These findings suggest that the influence of user reviews, influencer recommendations, and social media trends can increase the tendency for impulsive buying, but good self-control skills can reduce the influence of these social and psychological stimuli. The contribution of this research lies in testing a model of digital consumer behavior in purchasing skincare products on social media by positioning self-control as a control mechanism in the relationship between social and psychological factors on impulsive buying. The results of this study provide implications for skincare industry players to develop more responsible marketing strategies, and for consumers to improve their self-control abilities when faced with intensive exposure to digital marketing content.